PENGEMBANGAN MODUL DENGAN PENDEKATAN OPEN ENDED UNTUK MEMFASILITASI PENCAPAIAN LITERASI MATEMATIS - Agung Putra Wijaya (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2017)
This research and development aimed to develop module with an open ended approach to facilitate the achievement of mathematical literacy. This study was conducted only until the  field trial and the revision of product. The module was validated by experts with attention to aspects: matter, appearance, and practicality. Having been declared valid by experts, the test readability by the students was done. Based on the steps, it was obtained (1) the use of the module with an open ended approach in Linier Programmingwas expected by the students, (2) the module characteristics were in accordance with the curriculum and designed in accordance with the open-ended approach, (3) the experts responses to the module were appropriate in terms of aspects of matter, appearance, and practicality and (4) the students responses were good viewed by readability.